General discriminative optimization for point set registration. (February 2022) - Zhao, Yan; Tang, Wen; Feng, Jun; Wan, Taoruan; Xi, Long
Abstract: Point set registration has been actively studied in computer vision and graphics. Optimization algorithms are at the core of solving registration problems. Traditional optimization approaches are mainly based on the gradient of objective functions. The derivation of objective functions makes it challenging to find optimal solutions for complex optimization models, especially for those applications where accuracy is critical. Learning-based optimization is a novel approach to address this problem, which learns the gradient direction from datasets. However, many learning-based optimization algorithms learn gradient directions via a single feature extracted from the dataset, which will cause the updating direction to be vulnerable to perturbations around the data, thus falling into a bad stationary point. This paper proposes the General Discriminative Optimization (GDO) method that updates a gradient path automatically through the trade-off among contributions of different features on updating gradients. We illustrate the benefits of GDO with tasks of 3D point set registrations and show that GDO outperforms the state-of-the-art registration methods in terms of accuracy and robustness to perturbations. Graphical abstract: Highlights: Cast the point sets registration as a learning-based optimization problem. Utilize features of point sets to update gradients without the Hessian matrix. Collaborate the different features to reduce the influence of perturbations. Outperform the other advanced registration methods on accuracy and robustness.